Linkage between N2O emission and functional gene abundance in an intensively managed calcareous fluvo-aquic soil - Yang, Liuqing; Zhang, Xiaojun; Ju, Xiaotang (Scientific reports, 2017)
The linkage between N 2 O emissions and the abundance of nitrifier and denitrifier genes is unclear in the intensively managed calcareous fluvo-aquic soils of the North China Plain. We investigated the abundance of bacterial amoA for nitrification and narG, nirS, nirK , and nosZ for denitrification by in situ soil sampling to determine how the abundance of these genes changes instantly during N fertilization events and is related to high N 2 O emission peaks. We also investigated how long-term incorporated straw and/or manure affect(s) the abundance of these genes based on a seven-year field experiment. The overall results demonstrate that the long-term application of urea-based fertilizer and/or manure significantly enhanced the number of bacterial amoA gene copies leading to high N 2 O emission peaks after N fertilizer applications. These peaks contributed greatly to the annual N 2 O emissions in the crop rotation. A significant correlation between annual N 2 O emissions and narG, nirS , and nirK gene numbers indicates that the abundance of these genes is related to N 2 O emission under conditions for denitrification, thus partly contributing to the annual N 2 O emissions. These findings will help to draw up appropriate measures for mitigation of N 2 O emissions in this ‘hotspot’ region.